Selective targeting of histone methylation - Islam, Abul BMMK (Landes Bioscience, 2011)
Histones are post-translationally modified by multiple histonemodifying enzymes, which in turn influences gene expression. Much of the work in the field to date has focused on genetic, biochemical and structural characterization of these enzymes. The most recent genome-wide methods provide insights into specific recruitment of histone-modifying enzymes in vivo and, therefore, onto mechanisms of establishing a differential expression pattern. Here we focus on the recruitment mechanisms of the enzymes involved in the placement of two contrasting histone marks, histone H3 lysine 4 (H3K4) methylation and histone H3 lysine 27 (H3K27) methylation. We describe distribution of their binding sites and show that recruitment of different histone-modifying proteins can be coordinated, opposed or alternating. Specifically, genomic sites of the H3K4 histone demethylase KDM5A become accessible to its homolog KDM5B in cells with a lowered KDM5A level. The currently available data on recruitment of H3K4/H3K27 modifying enzymes suggests that the formed protein complexes are targeted in a sequential and temporal manner, but that additional, still unknown, interactions contribute to targeting specificity.